Type 1 diabetes: control and complications trials - Petrie, John (Henry Stewart Talks, 2015)
Type 1 diabetes and reduction in life expectancy, Tight glycaemic control and reduction of complications, Intensive insulin therapy association with hypoglycaemia and weight gain, “Non-insulin adjunct therapy” and relevant clinical trials